The association of sport specialization with youth ice hockey position and youth ice hockey parents` perceptions of sport specialization - Winans, M.; Biese, K. M.; Rudek, G.; Renner, M. N.; Stamm, J. M.; Bell, D. R. (International Journal of Athletic Therapy & Training, 2023)
Attitudes and beliefs of parents about sport specialization may indicate why youth athletes decide to specialize. The purpose of this study was to determine the association between sport specialization level, ice hockey position, and the parent/guardians` attitudes and beliefs on sport specialization. Our results demonstrate that goalies were the most likely to specialize, and parents of specialized ice hockey players tend to believe that sport specialization helps their child achieve future sporting aspirations. Increased sport specialization may put ice hockey goalies at an increased risk for overuse injuries, and parents` beliefs about sport specialization may impact their child`s sporting behaviors.